Interactive associations of smoking and physical activity with metabolic syndrome in adult men in Korea - Minjun Kim; Joonwoong Kim; Inhwan Lee; Inhwan Lee (Frontiers Media S.A., 2023)
IntroductionThis study aimed to investigate the association of smoking and physical activity (PA) with metabolic syndrome (MetS) in adult men in Korea.MethodsThis study analyzed data of 7,229 adult men aged 19-64 years obtained from the 2014-2021 Korea National Health and Nutrition Examination Survey (KNHANES). Information on smoking habits was obtained using KNHANES data, while that on total PA (TPA), leisure-time PA (LTPA), and occupational PA (OPA) was collected using the Global Physical Activity Questionnaire. Smoking status was classified into non-smokers and smokers, and PA was categorized into three groups (total, leisure time, and occupational) according to the time spent engaging in moderate or high-intensity PA areas. The diagnosis of MetS was based on the Adult Treatment Program III of the National Cholesterol Education Program and Koreans' waist circumference criteria.ResultsLogistic regression revealed that the risk of MetS was significantly lower in non-smokers than in smokers, even after adjusting for all covariates. The risk of MetS was significantly lower in individuals who engaged in at least 150 min of moderate- and high-intensity TPA or LTPA per week than in those who did not engage in PA. Furthermore, smokers who engaged in at least 150 min of moderate- to high-intensity TPA and LTPA per week had a significantly lower risk of MetS than those who did not engage in PA. Meanwhile, OPA was not associated with MetS.ConclusionThe findings suggest that engaging in moderate- to high-intensity TPA or LTPA for at least 150 min per week attenuates the risk of MetS caused by smoking.